2003
DOI: 10.1086/502258
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance for Hospital-Acquired Infections on Surgical Wards in a Dutch University Hospital

Abstract: Surveillance in four surgical wards showed that each had its own prominent infection, risk factors, and indications for specific recommendations. Because prospective surveillance requires extensive resources, we considered a modified approach based on a half-yearly point-prevalence survey of hospital-acquired infections in all wards of our hospital. Such surveillance can be extended with procedure-specific prospective surveillance when indicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…The host is susceptible to increased risk of infection due to immunosuppressive effect of steroids involving release of cytokines and other anti-inflammatory mediators. In our study, we found that systemic steroidal therapy plays an important role in contributing HAIs, and was compatible with other studies [30], [37].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The host is susceptible to increased risk of infection due to immunosuppressive effect of steroids involving release of cytokines and other anti-inflammatory mediators. In our study, we found that systemic steroidal therapy plays an important role in contributing HAIs, and was compatible with other studies [30], [37].…”
Section: Discussionsupporting
confidence: 93%
“…Another German study conveyed by Kamp-Hopmans et al found that the risk factors contributing HAI in surgical wards were: RR of enteral tube feeding over 48 hours was 6.6 (95% CI: 3.2–7.9) followed by ventilation used over 24 hours of 5.0 (95% CI: 3.2–7.9) and used of steroids of 3.4 (95% CI: 2.0–6.0) for respiratory infection; urinary catheter used for UTI was 3.9 (95% CI: 1.7–9.0) [30].…”
Section: Discussionmentioning
confidence: 99%
“…For example, a United States study estimated that S. aureus bacteraemia in this population was associated with a mortality rate of approximately 20%, with a mean additional health-care cost of approximately US$24,000. [83] Risk for infection varies according to the device type, with uncuffed catheters associated with the highest risk and native arteriovenous fistulae with the lowest risk. [84] Australian data support these findings, with rates of device-associated BSI of 0.4 per 1000 patient days for native fistulae, compared to 20.2 per 1000 patient days for non-tunnelled catheters.…”
Section: Patients Requiring Haemodialysismentioning
confidence: 99%
“…UMC Utrecht is a tertiary dardized prospective surveillance for hospital-acquired infec-care hospital with 1,042 beds for adults and children; aption was performed on 4 surgical wards from 1993 through proximately 27,000 admissions per year; 6 intensive care units 1997. 7 Although this survey provided detailed information (ICUs), including 2 pediatric ICUs; and all medical specialties about hospital-acquired infection in surgical patients, we…”
Section: Infect Control Hosp Epidemiol 2007; 28:459-465mentioning
confidence: 99%